Hurricane Andrew visits the maxwells... - Brewer, Bella (Cimarron, NM Cimarron Legend, 1992)
Article by Bella Brewer who talks about the Hurricane that her sister Margie Maxwell and family went through in Miami, Florida on August 24th.
Master List Item # 35
File location is in the New Mexico File Cabinets
Keywords: Maxwell, Margie; Charlie; Kathy; Maxwell, Calvin; Maxwell, Calvin ,Jr; Maxwell, Marilyn; Homestead Air Force Base; Hurricane; Family; Television; Devastation; Miami, Florida